BODY LANGUAGE IN BUSINESS NEGOTIATIONS: STRENGTHS AND WEAKNESSES - Melyana R Pugu; Nyi Dewi Puspitasari; Shafirah Fitri (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
This research discusses the influence of body language in business negotiations, with an emphasis on analyzing the strengths and weaknesses of using body language as a non-verbal communication tool. The research was conducted through a literature review method, which involved collecting data from various relevant journal articles, books and other publications on the subject. The results show that body language consistently plays a vital role in supporting the effectiveness of business negotiations, where non-verbal cues such as eye contact, gestures, and facial expressions can reinforce verbal messages and foster trusting relationships. However, the study also revealed that cultural differences and potential misunderstandings can be a drawback in the application of body language, often leading to conflict and inaccurate perceptions of prosperity. The recommendations from this study conclude that training and awareness on multi- cultural body language is an important aspect that needs to be integrated in business negotiation practices in order to maximize the strengths and mitigate the weaknesses of body language.